Arterial Hemodynamics of Two Phase Blood Flow for Medical Diagnostics (European Journal of Pure and Applied Mathematics, 2026)
Impact of thermal radiation on two-phase fluctuating blood flow and wall shear stress has applications in multiple directions. In medical science, areas such as hyperthermia, vascular diagnostics, and prosthetics benefit from advanced simulations of vascular behavior under thermal conditions. Wall shear stress (WSS), which arises due to the frictional force exerted by blood flow on arterial walls, plays a central role in regulating endothelial cell function and vascular homeostasis. Abnormalities in WSS are directly linked to the development and progression of atherosclerosis and other cardiovascular diseases. Specifically, regions with low or oscillatory WSS are more susceptible to plaque formation, while elevated WSS levels can lead to vascular remodeling or rupture of vulnerable plaques. In this study, electrically conducting dust particles that generate a high magnetic field are used to investigate how WSS affects two-phase fluctuating blood flowand heat transfer. An inclined channel with a certain inclination along the x-axis is used to model the flow. The flow in the channel is due to one of the walls fluctuating due to WSS. In order to investigate systematic solutions, the Poincar ́e-Lighthill perturbation technique (PLPT) isused. Mathcad-15 software is used to obtain the numerical results and related graphs. A graphic representation is presented to illustrate the effect of various embedded parameters on fluid and dust particle velocity profiles as well as temperature profiles. It is found that the increase in inclination angle controls both the flows. The boundary layer thins out with increased blood flow, decreasing both velocity profiles.
Keywords: Newtonian Heating; Blood Flow; Dusty Casson Fluid; Arbitrary Wall Shear Stress; Exact Solutions